Factors Influencing Continued Interest in Online Training with Learning Experience as Mediation - Aruan, Lenora Gustina; Siahaan, Elisabet; Silalahi, Amlys Syahputra (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study analyzes the factors influencing the continuance intention of online education and training at the Balai Pendidikan dan Pelatihan Keuangan Negara Medan with learning experience quality as a mediating variable. Using a quantitative approach, this study involved 291 online training participants as samples. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that system ease of use, system quality, and supervisor support positively influence online training continuance intention, both directly and through the mediation of online learning experience quality. The quality of online learning experience effectively mediates the influence of all three independent variables on online training continuance intention. This study provides recommendations for improving online training sustainability through the development of user-friendly systems, system quality enhancement, and strengthening supervisor support.